2017
DOI: 10.2214/ajr.16.16730
|View full text |Cite
|
Sign up to set email alerts
|

Utility of BI-RADS Assessment Category 4 Subdivisions for Screening Breast MRI

Abstract: OBJECTIVE BI-RADS for mammography and ultrasound subdivides category 4 assessments by likelihood of malignancy into categories 4A (> 2% to ≤ 10%), 4B (> 10% to ≤ 50%), and 4C (> 50% to < 95%). Category 4 is not subdivided for breast MRI because of a paucity of data. The purpose of the present study is to determine the utility of categories 4A, 4B, and 4C for MRI by calculating their positive predictive values (PPVs) and comparing them with BI-RADS–specified rates of malignancy for mammography and ultrasound. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 13 publications
0
34
0
Order By: Relevance
“…In all, 110 patients were excluded from our analysis based on our study eligibility criteria, whereby only lesions that were identified as enhanced mass lesions on DCE‐MRI with a histologic diagnosis were enrolled. Moreover, screening breast MRI is typically performed in high‐risk populations 34 . Thus, patients undergoing screening breast MRI typically have a significantly increased risk of malignancy compared with those who undergo typical mammography screening at clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In all, 110 patients were excluded from our analysis based on our study eligibility criteria, whereby only lesions that were identified as enhanced mass lesions on DCE‐MRI with a histologic diagnosis were enrolled. Moreover, screening breast MRI is typically performed in high‐risk populations 34 . Thus, patients undergoing screening breast MRI typically have a significantly increased risk of malignancy compared with those who undergo typical mammography screening at clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…A suspicious lesion detected by MRI performed for staging of a known cancer should be biopsied. There is ongoing research on the utility of BI‐RADS category 4 subdivisions for better stratification of the likelihood of malignancy in screening MRI . Our finding of the identification of benign US lesions will likely be of value for a subgroup of suspicious MRI lesions (category 4A, risk of malignancy >2 to ≤10%) detected during screening and shown to have benign US correlates.…”
Section: Discussionmentioning
confidence: 99%
“…The signs of the lesions are overlapping and intricate. These lesions, benign or malignant, are all classified as BI-RADS 4, along with recommended invasive procedures such as needle biopsy to obtain pathological evidence [7][8][9]. Therefore, comprehensive understanding and improved evaluation methods of benign and malignant breast lesions are urgently needed to reduce invasive operations and the burden on patients.…”
Section: Introductionmentioning
confidence: 99%